Vestibular epilepsy associated with a temporoparietal lobe meningioma in a cat - Rosanne K. Peters (Journal of Veterinary Internal Medicine)
Abstract A 15‐year‐old male castrated domestic shorthair cat presented with increasingly frequent vestibular episodes. The cat exhibited episodes of a head tilt, nystagmus, abnormal mental state, vocalizing, hypersalivation, restlessness, and vomiting. Episodes were <60 minutes long with normal inter‐episode condition. Systemic evaluations were generally benign. Magnetic resonance imaging documented a small meningioma in the left temporoparietal junction area with no other structural evidence of vestibular system pathologies. The episode frequency decreased with administration of levetiracetam which was discontinued 91 days post‐craniotomy. The cat had 2 more limited vestibular episodes: 1 at 211 days after craniotomy, and the second at 489 days after craniotomy. The cat maintained normal inter‐episode condition until it was euthanized for unrelated transitional cell carcinoma 907 days post‐craniotomy.